Naming something collective does not make it so: Algorithmic discrimination and access to justice - Jenni Hakkarainen (Internet Policy Review, 2021)
The article problematises the ability of procedural law to address and correct algorithmic discrimination. It argues that algorithmic discrimination is a collective phenomenon, and therefore legal protection thereof needs to be collective. Legal procedures are technologies and design objects that embed values that can affect their usability to perform the task they are built for. Drawing from science and technology studies (STS) and feminist critique on law, the article argues that procedural law fails to address algorithmic discrimination, as legal protection is built on data-centrism and individual-centred law. As to the future of new procedural design, it suggests collective redress in the form of ex ante protection as a promising way forward.
Keywords: 300; Access to justice; Collective redress; Algorithmic discrimination; Feminism; gender